An Ethnography of Bogotá's Ecobarrios the construction of place-based Eco-political Subjects, Subjectivities and Identities - Ome Baron, Aura Tatiana (Premio Internacional de tesis de investigación 2017. Transformación urbana. Densidad habitacional y ciudad compacta, 2017)
In the current global ecological crisis, environmental principles have become increasingly mainstreamed in urban politics and governance and in claim making processes across many cities in the global south. From an urban anthropology perspective, this involves interrogating how diverse actors use environmentalisms in order to generate (or not), what many define as alternative urban development trajectories that take nature into account. Inspired by this strand of work, this thesis examines how the search for such alternative trajectories impacts upon the construction of new ecological and political subjects, subjectivities and identities based on place in these times of change. As an anthropologist interested in cities, I offer here an ethnographic account of how the notion of Ecobarrios has opened different paths, in the construction of eco political subjects in Bogotá. Ecobarrios emerged as an institutional programme, which was implemented by the Mayor's Office between 2001 and 2003. It was later (2009) adopted as a local initiative by the dwellers of El Tríangulo in the eastern hills of the city; as a "resistance strategy" to avoid eviction and as a means to improve their living conditions. Following the different trajectories of these two attempts to articulate the notion of Ecobarrios to processes shaping urban life and territories in Bogotá. This thesis examines how the emergence of eco-political subjects either reproduced or challenged micro-political dynamics (of and from place) and how it gave rise to changes as well as transformations in urban planning. Conceptually and methodologically, the analysis fosters a debate about the scope, capacity as well as limitations of anthropology and ethnography in advancing our understanding of how different environmentalisms are pursued through urban planning processes and grassroots initiatives and with what consequences.